MODEL PENGANGKUTAN SAMPAH DI KOTA BANGLI - Sari Saraswati, Pande N; Sila Dharma, I G. B; Ketut Sudipta, I Gst (JURNAL SPEKTRAN, 2013)
The garbage transportation in Bangli City is currently done using a direct individual pattern (door to door). The vehicles used are dump trucks which are not covered, so they pollute the areas they pass by. Most of the vehicles are in bad condition. This study was aimed at identifying the transportation routes, the number of vehicles needed, the temporary place of garbage disposal ‘Tempat Pembuangan Sementara’ (TPS), and the rate of garbage retribution. The research method included the sample of garbage from the place of residence and the place of non residence based on SNI-19-3964-1994 used as a reference. This model used five compactor trucks for carrying garbage from 283 container bins with capacity of 0.36 m 3 , and one armroll truck for carrying the market garbage from four loudhaul with capacity of 6 m 3 per day. The amount of retribution is analyzed based on the calculation of investment feasibility for 10 years time at 18% MARR interest rate, with an assumption that there was subsidy from the government. It was found that the value of NPV (Net Present Value) was Rp. 35.673.540,99, the value of BCR (Benefit of Cost Ratio) was 1.021 and the value of IRR (Internal Rate of Return) was 19.11%. The monthly rates of retribution were Rp. 2,000.00/family, Rp. 20,000.00/school unit, Rp. 25,000.00/office unit, Rp. 8,000.00/shop unit, Rp. 20.000.00/restaurant unit, Rp. 2,000.00/hotel/accommodation unit, and Rp. 6,000.00/market trader.
Keywords: Model, Garbage Transportation, Vehicle, Investment, Retribution.